2004
DOI: 10.1074/jbc.m400129200
|View full text |Cite
|
Sign up to set email alerts
|

Distinct ADAM Metalloproteinases Regulate G Protein-coupled Receptor-induced Cell Proliferation and Survival

Abstract: Cross-talk between G protein-coupled receptor (GPCR) and epidermal growth factor receptor (EGFR) signaling systems is widely established in a variety of normal and transformed cell types. Here, we demonstrate that the EGFR transactivation signal requires metalloproteinase cleavage of epidermal growth factorlike growth factor precursors in fibroblasts, ACHN kidney, and TccSup bladder carcinoma cells. Furthermore, we present evidence that blockade of the metalloproteinase-disintegrin tumor necrosis factor-␣-conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
114
1
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(121 citation statements)
references
References 42 publications
5
114
1
1
Order By: Relevance
“…EGFR signalling appears important in the development of kidney cancer since inhibition of ADAM-17 by a dominant negative ADAM-17 mutant prevents pro-HB-EGF cleavage, EGFR activation and cell proliferation in kidney carcinoma cells [81]. As previously described in other types of cancers, ADAM-12 mRNA was found to be overexpressed in bladder cancer and ADAM-12 levels correlated with disease stage.…”
Section: Kidney Bladder Carcinomasupporting
confidence: 55%
See 1 more Smart Citation
“…EGFR signalling appears important in the development of kidney cancer since inhibition of ADAM-17 by a dominant negative ADAM-17 mutant prevents pro-HB-EGF cleavage, EGFR activation and cell proliferation in kidney carcinoma cells [81]. As previously described in other types of cancers, ADAM-12 mRNA was found to be overexpressed in bladder cancer and ADAM-12 levels correlated with disease stage.…”
Section: Kidney Bladder Carcinomasupporting
confidence: 55%
“…Among them, EGF receptor ligands (heparin-binding EGF (HB-EGF), amphiregulin, betacellulin, epiregulin) are synthesized as transmembrane precursors and require ectodomain shedding for activation [59,80]. ADAM-17 has been shown to play a key role in such a process [60,81]. Amphiregulin released by ADAM-17 cleavage enhances cell proliferation of cancer cells [82,83].…”
Section: Adams and Adamtss In Cell Proliferation And Apoptosismentioning
confidence: 99%
“…A number of investigators have shown that stimulation of GPCRs leads to release of HB-EGF and activation of the EGFR (Block et al, 2004;Pierce et al, 2001;Prenzel et al, 1999;Schafer et al 2004b;Shah et al 2004). Activation of the GPCRs can stimulate the ADAM family of matrix metalloproteases that release the EGFR ligands (Fischer et al, 2004;Yan et al, 2002;Schafer et al, 2004b).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the GPCRs can stimulate the ADAM family of matrix metalloproteases that release the EGFR ligands (Fischer et al, 2004;Yan et al, 2002;Schafer et al, 2004b). The use of metalloprotease inhibitors has been shown to block the release of EGFR ligands from cells (Tokumaru et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The ADAM-15 protein is involved in angiogenesis, because Adam15À/À mice show reduced tumor angiogenesis, and recombinant ADAM-15 disintegrin domain containing the RGD sequence inhibits angiogenesis, tumor growth, and metastasis (44). However, in breast tumors, ADAM-15 is localized primarily to the tumor cells themselves (26), indicating that its major actions are probably exerted on the cancer cell itself, potentially via modulation of integrinmediated cell adhesion or its proteolytic activity, such as its ability to transactivate the epidermal growth factor receptor by processing heparin-binding epidermal growth factor (8,45). Our analysis provides functional evidence for a role of variant ADAM-15 cytoplasmic tails in modulating cell adhesion and migration via their abilities to interact with different intracellular signaling effectors.…”
Section: Discussionmentioning
confidence: 99%